Between Party Democracy and Citizen Democracy : Explaining Attitudes of Flemish Local Chairs Towards Democratic Innovations - Caluwaerts, Didier; Kern, Anna; Reuchamps, Min; Valcke, Tony (Politics of the Low Countries, 2025)
As a response to the perceived legitimacy crisis that threatens modern democracies, local government has increasingly become a laboratory for democratic renewal and citizen participation. This article studies whether and why local party chairs support democratic innovations fostering more citizen participation. More specifically, we analyse the relative weight of ideas, interests and institutions in explaining their support for citizen-centred democracy. Based on the Belgian Local Chairs Survey in 2018 (albeit restricting our analysis to Flanders), the central finding is that ideas matter more than interests and institutions. Ideology is alive and kicking with regard to democratic innovation, with socialist and ecologist parties and populist parties being most supportive of participatory arrangements. By contrast, interests and institutions play, at this stage, a minor role in explaining support for participatory innovations.